The Fraud Trends Of Cyber Crime During 2020 And It’s Course of Action In Indian Penal Code, 1860 - Agarwal, Swati; Saluja, Khushi; Gautam, Bhavna (Trinity Law Review, 2022)
As borne out by the headlines cited above, the COVID-19 pandemic has turned out to be the dominant theme in the recent upsurge of cyber crime. The vital dependency on virtual environments through organizations and individuals during the COVID-19 pandemic is being exploited by cyber criminals. Cyber crime is not a new concept to the world, as it has been present throughout the ages and has become a major issue in modern society - as due to the advancement of technology4, the dependency on the internet has rapidly increased, which has resulted in issues related to cyber crime. It differs from other types of crime that occur in the modern era, as ‘the cybercrime has no boundaries’, is a much wider idea as it is used to define criminal activity that is executed with the help of computers, electronic devices, etc. It covers crimes like phishing, bank robbery, illegal phishing, credit card fraud, and so on.5The first major wave of cybercrime was recorded in the late 1980s, when it enabled the host to deliver malware in your inbox. The subsequent wave was observed in the 1990s with the development of web browsers. In only 20 years, cyber-crime has turned out to be common in our society. The statistics is used in order to overdraw bank accounts, credit cards, and other financial fraud.6
Keywords: Cyber Crime; Indian Penal Code